State of Haemodynamics in Athletes with Musculoskeletal Disorders Involved in Various Types of Physical Activity - Viktoriya V. Kalsina; Olga N Kudrya (Журнал медико-биологических исследований)
Adequate haemodynamic indices for the body’s optimal functioning during physical activity is the main condition for an athlete’s effective performance. In healthy athletes, certain changes in the circulatory system due to the type of exercise occur, which are not always of a positive adaptive nature. For athletes with musculoskeletal disorders, such changes are poorly described in literature. The purpose of this study was to assess haemodynamic changes in athletes with musculoskeletal disorders depending on the type of physical activity. Materials and methods. The research involved 93 people, including 52 athletes with various forms of musculoskeletal disorders and 41 healthy athletes. The mean age of athletes with musculoskeletal disorders was 27.4 ± 4.1 years, and that of healthy athletes was 25.3 ± 1.5 years. The length of training was 5.4 ± 1.2 and 7.3 ± 2.6 years, respectively. During the 1st stage of the research, we used baseline haemodynamic values to analyse the state of the circulatory system in athletes with musculoskeletal disorders and healthy subjects doing various types of exercises in their training process. The 2nd stage involved studying changes in the functional haemodynamic resources of athletes with musculoskeletal disorders in response to a graded exercise test. Results. At rest, peripheral haemodynamic indices (systolic blood pressure, mean arterial pressure, and peripheral vascular resistance) in athletes with musculoskeletal disorders were found to be higher, while central haemodynamic indices (stroke volume and cardiac output) lower than in healthy athletes. Physical load activates resources allowing the cardiovascular system to work more intensely in athletes with musculoskeletal disorders. We found that haemodynamic changes in groups of athletes with musculoskeletal disorders correspond to those in groups of healthy athletes with a similar focus of the training process. In athletes with musculoskeletal disorders, the most negative changes in haemodynamics and strain of the adaptive mechanisms are caused by the predominance of static exercises and strength training.